Pengaruh Limbah Industri Tahu Terhadap Kualitas Air Sungai Berdasarkan Parameter Biochemical Oxygen Demand, Chemical Oxygen Demand, Total Suspended Solid (Studi Kasus Industri Tahu di Dusun Janten, Ngestiharjo, Kasihan, Bantul) - Sardono, Dimas Ari; Sutrisno, Widarto; Sulistyorini, Dewi; Anwar, Aristu; Anggraini, Rizki Budi (Proceedings Series on Physical & Formal Sciences, 2023)
This research aims to evaluate the influence of wastewater treatment plant (WWTP) outlets on the water quality of the Kalibayem River in the Dusun Janten, Ngestiharjo, Kasihan, Bantul area. The research method employed involved collecting river water samples from points before and after the WWTP outlets, as well as analyzing water quality parameters such as BOD, COD, and TSS. The research findings indicate that the WWTP outlets have a significant impact on the water quality of the Kalibayem River. After undergoing treatment processes at the WWTP, there was a reduction of 0.85% in BOD, 1.28% in COD, and 62% in TSS levels in the river water. Thus, the results of this study demonstrate that the WWTP outlets of the tofu industry do not have a significant impact on pollution in the Kalibayem River in the Dusun Janten, Ngestiharjo, Kasihan, Bantul area. This means that the WWTP has been successful in reducing pollution loads and maintaining the water quality of the river. The implications of this research can be used as a reference for managing and controlling industrial waste and preserving the sustainability of the river ecosystem in that area.